2022
DOI: 10.3390/jcm11216433
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Patients with Peripheral Artery Disease Influenced by COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic influences the health care management of acute and chronic diseases. Data concerning the influence of the pandemic on hospitalizations of patients with peripheral artery disease (PAD) are sparse. Methods: We analysed all patients hospitalized due to PAD between 1 January 2019 and 31 December 2020 in Germany. Hospitalizations of PAD patients during the pre-pandemic year 2019 were compared to the pandemic year 2020. Results: Overall, 361,029 hospitalizations of PAD patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…This finding of increased revascularisations however, is not consistent with the existing, albeit scarce, literature on the topic where a decline in revascularisation for PAD has been observed during the pandemic [22][23][24]. However, many of these studies only evaluated the first wave of the pandemic therefore a potential increase in numbers due to delayed presentations and referrals cannot be excluded.…”
Section: Discussioncontrasting
confidence: 83%
“…This finding of increased revascularisations however, is not consistent with the existing, albeit scarce, literature on the topic where a decline in revascularisation for PAD has been observed during the pandemic [22][23][24]. However, many of these studies only evaluated the first wave of the pandemic therefore a potential increase in numbers due to delayed presentations and referrals cannot be excluded.…”
Section: Discussioncontrasting
confidence: 83%
“…Others have reported that admissions for MI were significantly reduced during the COVID-19 pandemic, with a parallel increase in fatality and complication rates [10][11][12]. Numbers of hospital admissions of PAD patients were also reduced [13].…”
Section: Introductionmentioning
confidence: 95%